MODERN METHODS OF TEACHING TRADITIONAL PERFORMING ART TO HIGHER EDUCATION STUDENTS - No‘monov Iftixorjon Iqboljon o‘gli (European Science Publishing, 2024)
In this article, the effective use of modern methods of education (in particular, interactive), pedagogical and information and communication technologies in the creative educational process. Computers of information resource centers, information resource networks such as "Internet", "Zionet", effective use of pages of special websites, special educational literature - textbooks, training manuals, methodical manuals, methodical recommendations, sheet music extensive use of practical computer programs is envisaged.
Keywords: Information resource, status, sheet music, website, world pop.